Strengthening Mosque-Based Religious Education through Community Development and the Training of Trainers for Facilitator Cadres - Marpuah; Hasanudin, Muhamad Ihsan; Yusran Azmi, Naufal; Shafa Zaidan Al Wahyudi, Afifah (Edumedia Solution, 2026)
This community service program aimed to establish an initial governance foundation for mosque-based religious education in Cinarusa Hamlet, Mandalawangi Village, Nagreg District, Bandung Regency. The program was initiated in response to the strong dependence of religious activities on particular individuals, the absence of simple operational tools, and the limited readiness of local cadres to support program sustainability. The activities were implemented through a participatory community development approach combined with training of trainers (ToT) and experiential learning. The preparation stage included initial coordination, field observation, participatory discussions, and informal interviews to identify the needs of the community partners. The core activities were conducted on February 7, 2026, involving 25 participants consisting of DKM members, prospective facilitator cadres, and representatives of the congregation and majelis taklim. The program implementation included restructuring the management system of mosque-based religious education, training facilitator cadres, conducting facilitation simulations, finalizing operational tools, and carrying out joint reflection. The results showed the establishment of an initial coordinating team structure, the development of a three-month activity calendar and a simple SOP for preventing activity cancellation, the implementation of ToT for core cadres, and the preparation of a concise facilitator module and basic administrative tools. Overall, the program produced an initial operational foundation that supports stronger governance, cadre development, and the sustainability of mosque-based religious education in a more structured and participatory manner